Influence of piston displacement profiles on the performance of a novel dual piston linear compressor. (September 2020) - Wei, Yidi; Zuo, Zhengxing; Jia, Boru; Feng, Huihua; Liang, Kun
Highlights: A novel dual piston linear compressor is presented. The influence of typical displacement profiles is studied by a numerical model. Triangle profile has the highest isentropic and electrical efficiency. The influence of back electromagnetic force cannot be ignored. Abstract: A novel dual piston linear compressor has been proposed in this paper, which is suitable for various applications such as refrigeration and gas compression owing to capacity modulation by stroke control. A numerical model for the proposed dual piston linear compressor was built to investigate the influence of different piston displacement profiles on the performance of the linear compressor. Sub-models on the piston dynamics, cylinder gas thermodynamics, motor force and frictional force were presented using MATLAB/Simulink. The piston was controlled to oscillate with the 5 typical piston displacement profiles. From the simulation results, it is found that the displacement profile of a triangle curve shows the highest compression efficiency and highest electrical efficiency. Moreover, the piston velocity and the current in the coil of the linear motor are considered to be necessary for feedback signals in the real-time control system to adjust the motor force and to reduce the effect of the back electromagnetic force.